FORMULATION AND EVALUATION OF CHITOSAN-POLYPYRROLE NANOCOMPOSITES FOR CONTROLLED RELEASE OF ANTICANCER DRUG DOXORUBICIN - BEHERA, DILLIP KUMAR; MISHRA, KAMPAL (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of the present study was a characterization of chitosan (CS)-polypyrrole (PPY) nanocomposites for controlled release of anticancer drug doxorubicin (DOX). Methods: Chitosan crosslink with PPY with montmorillonite (MMT) called as (CS-PPY/MMT) were formulated using the solvent casting method. The prepared nanocomposites were characterized by X-Ray Diffraction Analysis (XRD), tensile strength, scanning electronic microscope (SEM). Results: The XRD result confirmed that the CS-PPY/MMT possessed crystal structure. The nanocomposites CS-PPY/MMT-4 were showed a homogenous morphology. The Water uptake and swelling ratio of the CS-PPY and CS-PPY/MMT were found to decrease with increase in the concentration of clay. Mechanical properties of the CS-PPY and CS-PPY/MMT were assessed in terms of tensile strength and extensibility using texture analyzer. Increase in tensile strength and reduction in extensibility was reported with an increase in the nanoclay content. In vitro drug release study on CS-PPY and CS-PPY/MMT indicated pronounced sustained release of doxorubicin by the incorporation of clay particles in CS-PPY/MMT. It was observed that during the first 60 min of the dissolution study, the CS-PPY/MMT-4 film showed just 79.32±0.56% drug release as while the CS-PPY-1, CS-PPY/MMT-2 and CS-PPY/MMT-3 films showed a release of 53.79±1.23%, 63.51±1.24% and 68.15±2.38% respectively. Conclusion: CS-PPY/MMT nanocomposite films exhibited improved mechanical and sustained drug release properties than CS-PPY. The combination of biodegradable polymeric chains and clay reinforcement can be applied to achieve the desired combination of properties of materials used as a biosensor for diverse biomedical applications.